Jews, Gentiles and the church a new perspective on history and prophesy - Larsen, David (Grand Rapids, MI Discovery House, 1995)
Includes biliographical references and index.
Keywords: Bible -- prophecies -- Jews; Judaism (Christian theology).; Palestine in Christianity; Israel (Christian theology).